PEMBELAJARAN KETERAMPILAN MENULIS MELALUI PENDEKATAN PROSES DAN MODEL PROBLEM BASED LEARNING - Mia Apta Candra.S; Silvina Noviyanti; Ahmad Syarif; Gress Vinessa Simorangkir (STKIP Subang, 2026)
Writing skills are an essential competency in Indonesian language learning, playing a significant role in developing students’ critical thinking and communication abilities. However, various studies indicate that students’ writing skills remain relatively low, particularly in generating ideas and organizing texts systematically. This study aims to analyze the teaching of writing skills through the process approach (prewriting, drafting, revising) and the Problem Based Learning (PBL) model based on recent literature. The method used is a literature review by analyzing relevant scholarly articles published between 2020 and 2024. The results of the review show that the writing process approach can gradually improve the quality of students’ writing, while the PBL model is effective in enhancing students’ motivation and critical thinking skills. The integration of both approaches provides a more optimal impact on writing skills. Therefore, process-based and contextual problem-based writing instruction is recommended for implementation in elementary schools.